Climate finance readiness: A review of institutional frameworks and policies in Kenya. Issue 1 (31st December 2022) - Kiremu, Mercy; Scrimgeour, Frank; Mutegi, James; Mumo, Richard
ABSTRACT: A significant increase in low carbon investments is required to limit global warming to less than 2° C. For example, about USD 900 billion should be invested annually in the energy sector up to 2030 to meet this target. Climate finance provides opportunities for investments in climate-smart projects. Such investments could enhance Africa's adaptive capacity, food security and economic growth. Nonetheless, Africa lags behind in the access and utilisation of these funds. Climate finance readiness plays a major role in enhancing access to these funds. This paper analyses policy and institutional frameworks that would enhance Kenya's readiness for climate finance. Publicly available scholarly articles, government and development partners reports were profiled using the following key words: Kenya, climate change, climate mitigation and climate adaptation. Then the keywords; climate finance, climate policy and legislation were used to identify the most relevant publications. These were reviewed to assess Kenya's readiness for climate finance. The study finds that considerable efforts have been made to enhance Kenya's readiness for climate finance as evidenced by the formulation of climate-related policies, legislation and the creation of institutions tasked to address climate change. Nonetheless, some policy areas could be enhanced. For instance, the role of the private sector could be better recognised and supported. This study provides an important reference for the government, development partners and private sector involved in negotiations and decision making on climate financing in Kenya.